Saccharomyces Kluyveri Fungemia in a Patient with Human Immunodeficiency Virus Infection - Elleuch E.; Hammami M.; Marrekchi C.; Cheikhrouhou Fatma; Trabelsi H.; Maâlej M.; Hammami B.; Maaloul I.; Ayedi A.; Lahiani D.; Ben Jemaa M. (Journal of Fungal Diversity, 2018)
We report a case of a young woman with acquired immune deficiency syndrome admitted with fever and abdominal pain. Saccharomyces kluyveri was isolated in blood culture. She was successfully treated with fluconazole. This case demonstrates the pathogenicity of Saccharomyces Kluyveri in immunocompromised host.
Keywords: AIDS